2007
DOI: 10.1270/jsbbs.57.243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the High-Molecular-Weight Glutenin Allele, Glu-D1d, on Noodle Quality of Common Wheat

Abstract: In the southwestern part of Japan, weakness of the dough produced from soft wheat used for white salted noodles, resulting from low protein content and poor protein quality, is one of the shortcomings in noodle quality. We investigated the effect of the high-molecular-weight glutenin allele, Glu-D1d, on dough properties and noodle quality using near-isogenic lines (NILs) of three soft wheat cultivars. The NILs with the GluD1d allele showed significantly stronger dough, based on the sodium dodecyl sulfate sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 17 publications
1
5
0
2
Order By: Relevance
“…Glu-B1 Glu-D1 Glu-A3 Glu-B3 Glu-D3 W (10 -4 J) P/L (0.1 -6.0) , 2+12, b, h, c, vs 1, 17+18, 5+10, b, h, c, where one allele is replaced by 2* in Glu-A1 and 5+10 for 2+12 in Glu-D1, increasing the kneading time, which is consistent with the results reported by Radovanovic et al (2002) and Zheng et al (2009) associated the allele 5+10 with the highest values of kneading time compared to 2+12, while Yanaka et al (2007) associated that with an increased sedimentation volume.…”
Section: Gapm Gbpm Glu-a1supporting
confidence: 89%
See 1 more Smart Citation
“…Glu-B1 Glu-D1 Glu-A3 Glu-B3 Glu-D3 W (10 -4 J) P/L (0.1 -6.0) , 2+12, b, h, c, vs 1, 17+18, 5+10, b, h, c, where one allele is replaced by 2* in Glu-A1 and 5+10 for 2+12 in Glu-D1, increasing the kneading time, which is consistent with the results reported by Radovanovic et al (2002) and Zheng et al (2009) associated the allele 5+10 with the highest values of kneading time compared to 2+12, while Yanaka et al (2007) associated that with an increased sedimentation volume.…”
Section: Gapm Gbpm Glu-a1supporting
confidence: 89%
“…entre 2*, 17+18, 2+12, b, h, c, vs 1, 17+18, 5+10, b, h, c, donde se sustituyeron los alelos 1 por 2* en Glu-A1 y 5+10 por 2+12 en Glu-D1, aumentaron el tiempo de amasado, lo cual coincide con lo señalado por Radovanovic et al (2002) y Zheng et al (2009) asociaron al alelo 5+10 con valores más altos de tiempo de amasado respecto a 2+12; mientras que Yanaka et al (2007) lo relacionaron con mayor volumen de sedimentación. Cuadro 4.…”
Section: Gapm Gbpm Glu-a1unclassified
“…The monomeric gliadin fraction had the opposite relationship. In contrast, Yanaka et al 55 reported that although protein content was negatively correlated with color, specific glutenin genes were not.…”
Section: Effect Of Flour Proteinmentioning
confidence: 92%
“…American Association of Cereal Chemists (AACC, 1990) methods [ 26 ] were followed for evaluation of moisture, ash and protein content. Size-exclusion high-performance liquid chromatography (SE-HPLC) was carried out for determination of unextractable polymeric proteins [ 27 ]. Briefly, for extractable proteins, the flour suspension (10 mg of flour in 1.0 ml of 0.5% w/v SDS-phosphate buffer, pH 6.9) was stirred for 5 min (without sonication) and the supernatant was collected.…”
Section: Methodsmentioning
confidence: 99%